Subsídios para o gerenciamento de resíduos sólidos urbanos nos municípios de Padre Paraíso e Francisco Badaró - Vale do Jequitinhonha (MG) - Camila Moreira de Assis (2007)
The necessity of enabling and investing in improvements in the municipal solid waste (MSW) management are evident for many Brazilian cities, including the ones that compose the interior of Minas Gerais. In the average valley of the river Jequitinhonha the situation is not different, since the region is devoid in many other aspects, as social and the economic one. Projects that work the municipal solid waste integrated management (MSWIM) involve some instruments, including them of environmental education. This thesis considers the generation of subsidies that help to improve and to strengthen the MSWIM in two cities of the average Valley of the Jequitinhonha, Francisco Badaró and PadreParaíso (MG), being distinguished it necessity of proposals in environmental education. The research was divided in methodology stages, that they had approached since the diagnosis of the local realities of the cities, occurred between July of 2005 and November of 2006, through visits the field, consults documents, registers of photographs and questionnaires, until the data-collecting in state and federal level, as laws and initiatives in environmental education, carried through of April the July of 2006. In the municipal scope, they have beengiven regarding the general conditions of the management of MSW, the initiatives in environmental education and its respective social actors, beyond the local laws and the organizational structure of the City halls.The results even so raise imperfections, as still the inefficient joint between the local social actors, the abrupt interruption of the projects and the inexistence of evaluation mechanisms and accompaniment of the activities , point positive points of the actions that already are practised in the cities: significant number of initiatives and involved and/or available social actors, great influence of external actors, easiness of access and interaction with the interviewed actors, and some interest on the part of the City halls, strengthening the idea of that the local intentions are significant and positive, having to be detached and to be valued.Initiatives in environmental education, also those that work the solid waste, need well to be planned and to be structuralized with the city, in order to reach resulted satisfactory and to gain the credibility of the population. The necessity to plan actions that mobilize the city all,but that they have continuity and they can count on the participation of the people, also is evident, as well as the identification of the involved social actors and the stimulaton for its joint and participation in the process.